Analysis of Factors Affecting the Level Of E-Government Implementation in West Java - Syaiful Ikhsan; Nunuy Nur Afiah; Ivan Yudianto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
In order to increase public accountability, transparency, and so that the government is more effective and efficient in running the government. Local governments use a tool called e-government. Not only has the objectives of transparency and accountability, the use of e-government application systems is expected to be able to improve the performance of local governments to be more economical, efficient and effective. This study aims to examine the effect of PAD, capital expenditure, financing revenue, PDRB, education level, and population factors on the e-government index value. Data analysis used linear regression analysis with quantitative research methods. The results of the study based on linear regression indicate that the PAD, capital expenditure, financing revenue, PDRB, and population factors have a positive effect on the e-government index value in regency / municipal governments in West Java.